57. CURRENT STATE OF KNOWLEDGE AND PRACTICE OF PARENTS WHO HAVE CHILDREN WITH AUTISM AT THE CENTRAL ACUPUNCTURE HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge, attitudes and practices of parent’ s autism.Subjects and methods: Cross-sectional study with 220 parents, who have a child with autism participate in survey at the National Hospital of Acupuncture in 2025.Results: Regarding knowledge about autism, 60% of parents knew the definition of autism, 43.18% of parents recognized typical symptoms, but only 17.27% clearly understood the causes of autism. Regarding the attitudes of parents with autistic children, 48.64% parents were worried when thinking about their children’s future, but they have a positive outlook, believing in the value of early intervention and opportunities for social integration for their children (52.73% and 52.27% of parents are proud to see their children’s progress. Regarding parents’ practices towards autistic children, they proactively support their children in basic activities: 76.82% of parents help their children participate in outdoor activities, 51.82% of parents guide their children to use support tools such as toothbrushes and mouthwash cups, but there are still limitation in accessing specialized support services (23.64%) and community connections (35.91%).Conclusion: It is necessary to further improve the understanding of parents with autistic children about knowledge, attitudes and practices to have appropiate behavior, contributing to improving the effectiveness of interventions for autistic children.
Keywords: Knowledge; attitude; behavior; autism.